Diagnosis of Gestational Diabetes Mellitus with Point-of-Care Methods for Glucose versus Hospital Laboratory Method Using Isotope Dilution Gas Chromatography-Mass Spectrometry as Reference - Karl Kristensen; Anne-Marie Wangel; Anastasia Katsarou; Nael Shaat; David Simmons; Helena Fadl; Kerstin Berntorp (Journal of Diabetes Research)
Background. In Sweden, both glucose analyzers in accredited laboratories and point-of-care glucose devices are used for gestational diabetes mellitus (GDM) diagnosis. The aim of this study was to compare the diagnostic performance of the HemoCue Glucose 201+ (HC201+) and RT (HC201RT) systems with that of the hospital central laboratory hexokinase method (CL) based on lyophilized citrate tubes, using the isotope dilution gas chromatography-mass spectrometry (ID GC-MS) as reference. Methods. A 75 g oral glucose tolerance test was performed on 135 women screened positive for GDM. Diagnosis was based on the World Health Organization 2013 diagnostic thresholds for fasting (n=135), 1 h (n=52), and 2 h (n=135) glucose measurements. Bland-Altman analysis and surveillance error grids were used to evaluate analytical and clinical accuracy. Results. Significantly more women were diagnosed with GDM by HC201+ (80%) and CL (80%) than with the reference (65%, P<0.001) based on fasting and/or 2 h thresholds, whereas the percentage diagnosed by HC201RT (60%) did not differ significantly from the reference. In Bland-Altman analysis, a positive bias was observed for HC201+ (4.2%) and CL (6.1%) and a negative bias for HC201RT (−1.8%). In the surveillance error grid, 95.9% of the HC201+ values were in the no-risk zone as compared to 98.1% for HC201RT and 97.5% for CL. Conclusions. A substantial positive bias was found for CL measurements resulting in overdiagnosis of GDM. Our findings suggest better performance of HC201RT than HC201+ in GDM diagnosis. The results may have possible implications for GDM diagnosis in Sweden and require further elucidation.